Editorial - Núñez Vergara, Manuel (2015)
Human resources are the cornerstone of the health system. This staff with their daily work expresses the values and principles, the warmth and quality that the user directly receives and perceives in services. The reform that is underway in the health sector plays its fate largely to the extent that achieves these staff with their enthusiasm, concerns, abilities and desires commitment to reform. That is why a human resources agenda requires constructed converge looks and priorities of managers, users and workers, which highly complex coating is an unavoidable challenge.